Inviting Culture into Her Wellness: The Moderating Effects of African Centered Coping on Suicide Risk Factors Among Black Women - Oliphant, Vanessa; Wingate, LaRicka; Benson, Olufunke (Journal of Ethnic and Cultural Studies, 2025)
There is a need for greater emphasis to be placed on the lived experiences of Black women in psychological research, and more specifically, Black women’s experiences with suicide ideation. Despite having the lowest suicide rates, prior research indicates an increase in suicide ideation among Black women and girls. The current study aims to evaluate the moderating effects of Black women’s implementation of culturally specific ways of coping (i.e., Africultural coping skills) to pinpoint protective strategies against interpersonal suicide risk factors, thwarted belongingness, and perceived burdensomeness. 99 (M age = 23) cisgender African American/Black women were surveyed, and results indicated that spiritual centered coping both significantly and negatively moderated the relationship between perceived burdensomeness and suicide ideation (B = -0.00, t = -2.29, p = .02, 95% CI [-.0085, -.0006]). Additionally, ritual centered coping significantly and negatively moderated the relationship between perceived burdensomeness and suicide ideation (B = -.009, t = -2.05, p = .04, 95% CI [-.0179, -.0003]). Findings suggest that spiritual and ritual centered coping can be protective strategies for Black women by weakening the relationship between suicide ideation and the interpersonal suicide risk factor perceived burdensomeness.